2020
DOI: 10.3390/su12135445
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Deficiency-Dependent Abiotic Stress Enhances Carotenoid Production in Indigenous Green Microalga Scenedesmus rubescens KNUA042, for Use as a Potential Resource of High Value Products

Abstract: The microalgal strain Scenedesmus rubescens KNUA042 was identified in freshwater in Korea and characterized by evaluating its stress responses in an effort to increase lipid and carotenoid production. Under a two-stage cultivation process, the algal strain that generally exhibits optimal growth at a nitrate (source of nitrogen) concentration of 0.25 g L−1 was challenged to different exogenous stimuli—salinity (S), light intensity (L), combined L and S (LS), and nitrogen deficiency (C)—for 14 days. Lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…The fatty acid profile of H. rubescens also shows that this microalga is suitable for biodiesel production, as well as cosmetic and pharmaceutical applications. Similarly, the fatty acid profile of Scenedesmus rubescens KNUA042 includes major fatty acids such as palmitic acid, oleic acid and linoleic acid (Jo et al 2020). Lin et al (2012) reported the profile of S.…”
Section: Discussionmentioning
confidence: 98%
“…The fatty acid profile of H. rubescens also shows that this microalga is suitable for biodiesel production, as well as cosmetic and pharmaceutical applications. Similarly, the fatty acid profile of Scenedesmus rubescens KNUA042 includes major fatty acids such as palmitic acid, oleic acid and linoleic acid (Jo et al 2020). Lin et al (2012) reported the profile of S.…”
Section: Discussionmentioning
confidence: 98%
“…Carotenoid composition and content for this alga depends on strain and/or culturing conditions. Jo et al [ 189 ] reported that the main secondary carotenoids were canthaxanthin and astaxanthin ( Table 1 ). Their contents after carotenogenesis induction are c.a.…”
Section: Diversity and Distribution Of Unicellular Carotenogenic Algaementioning
confidence: 99%
“…Nitrogen concentration is an important factor that regulates biomass or carotenoid productivity in microalgae (Jo et al 2020, Minyuk et al 2020. Because nitrogen is a major component of proteins, nitrogen-deficient conditions cause retardation or terminate cell growth and trig-…”
Section: Characteristics Of the Oh214 Strain Under Nitrogen Supplymentioning
confidence: 99%
“…5E). Therefore, the high carotenoid content per cell number in nitrogen-deficient culture can be explained by the enlarged cell size due to the inhibition of cell division (Jo et al 2020, Minyuk et al 2020, Yaakob et al 2021). These results indicate that nitrogen shortage can induce carotenoid accumulation; therefore, nitrogen-deficient cultivation is suitable for the production of β-carotene and lutein together from the D. salina OH214 strain.…”
Section: Growth Phase Kno3 (Mm)mentioning
confidence: 99%